Parent-Teacher Partnership for Gifted Early Readers in New Zealand - Margrain, Valerie (International Journal about Parents in Education, 2023)
The experiences of gifted preschool readers and their parents are discussed in this paper, with data obtained through extended parent interviews of 11 four-year-old children in New Zealand (Margrain, 2005). In addition to sharing the experiences of these parents, common misconceptions are reported, and the positive role that parents play in supporting their children highlighted. Findings indicate that the parents were able to identify their children’s strengths and talents, acted as advocates to support their children, were responsive, and provided the key resource of time. These findings negate commonly held assumptions that the parents of gifted children are overtly ‘pushy’ or ‘hothousing’. Instead, this paper argues that teachers can learn a lot from parents and they need to work together to plan for positive outcomes for young gifted children.